FOSTERING SOCIAL HARMONY IN DIVERSITY: INTER-ETHNIC INTERACTIONS AMONG SASAK, BALI, AND SAMAWA COMMUNITIES IN LUNYUK DISTRICT, SUMBAWA - Muhammad Malthuf; Desi Kurnia Fitri (SOCIETY, 2026)
This study examines the inter-ethnic interactions among the Sasak, Balinese, and Samawa communities in Lunyuk Subdistrict, Sumbawa, to understand how social harmony is maintained amidst cultural and religious diversity. The research is significant as it sheds light on practical strategies for fostering coexistence in rural multicultural settings, contributing novel insights into community resilience and interdependence. The study aims to identify the forms of social interaction across economic, agricultural, and cultural domains while addressing the challenges posed by differences in language, customs, and religion. Using a qualitative case study approach, data were collected through non-participant observations, semi-structured interviews with 15 informants, and documentation. The analysis was conducted using data triangulation to ensure validity and reliability. The findings reveal that trading, agricultural collaboration, and cultural events are vital avenues for strengthening inter-ethnic relationships. Key challenges include linguistic barriers and differing cultural practices, which are mitigated through mutual respect, empathy, and effective communication. The study highlights the importance of adaptive strategies in sustaining harmony and provides a model for addressing diversity-related challenges in similar settings. These insights have implications for community development and policy- making in multicultural societies, promoting inclusivity and cohesion in both rural and urban contexts. Keywords: Bali ethnic group; Culture diversity, Social interactions, Sasak ethnic group, Samawa ethic group.